Влияние наночастиц и ионов металлов на выживаемость и пролиферацию стволовых клеток человека in vitro - Папуга, А.Е.; Самченко, Ю.М.; Сухорада, Е.М.; Рубан, Т.А.; Коломиец, Ю.Н.; Зенич, А.В.; Уварова, И.В.; Ульберг, З.Р.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2015)
Aims. The development of new therapeutic agents and biotechnological tools with nanomaterials in their compositions is perspective and promising field. Thus, the aim of our study was to investigate the effect of nanoscale particles or ions of some metals on the survival and proliferation of cells in vitro. Methods. We used human stem cell line 4BL. Cells were incubated in the presence of nanoparticles (Fe₃O₄, Ag) and metal ions (Mn²⁺, Zn²⁺). Proliferative activity of the cells was determined by MTT assay or direct counting the cells in suspension. Results. Metal nanoparticles and ions at certain concentrations increased the number of metabolic active cells as compared to control cell populations. Conclusions. Our data evidence that the nanoparticles (Fe₃O₄, Ag) and the metal ions (Mn²⁺, Zn²⁺) used in our experiments were to be able to influence on the survival and the proliferation of the cells in concentration dependent manner